Synergism between SLC6A14 blockade and gemcitabine in pancreactic cancer: a 1H-NMR-based metabolomic study in pancreatic cancer cells. Issue 10 (29th May 2020) - Cai, Aimin; Zheng, Hailun; Chen, Zhiwei; Lin, Xinlu; Li, Chen; yao, Qing; Bhutia, Yangzom D.; Ganapathy, Vadivel; Chen, Ruijie; Kou, Longfa
Abstract : Gemcitabine is the first-line chemotherapy for pancreatic cancer. To overcome the often-acquired gemcitabine resistance, other drugs are used in combination with gemcitabine. It is well-known that cancer cells reprogram cellular metabolism, coupled with the up-regulation of selective nutrient transporters to feed into the altered metabolic pathways. Our previous studies have demonstrated that the amino acid transporter SLC6A14 is markedly up-regulated in pancreatic cancer and that it is a viable therapeutic target. α-Methyltryptophan (α-MT) is a blocker of SLC6A14 and is effective against pancreatic cancer in vitro and in vivo . In the present study, we tested the hypothesis that α-MT could synergize with gemcitabine in the treatment of pancreatic cancer. We investigated the effects of combination of α-MT and gemcitabine on proliferation, migration, and apoptosis in a human pancreatic cancer cell line, and examined the underlying mechanisms using 1 H-NMR-based metabolomic analysis. These studies examined the intracellular metabolite profile and the extracellular metabolite profile separately. Combination of α-MT with gemcitabine elicited marked changes in a wide variety of metabolic pathways, particularly amino acid metabolism with notable alterations in pathways involving tryptophan, branched-chain amino acids, ketone bodies, and membrane phospholipids. The metabolomic profiles of untreated control cells and cells treated with gemcitabine or α-MT were distinctly separable, and the combination regimen showed a certain extent of overlap with the individual α-MT and gemcitabine groups. This represents the first study detailing the metabolomic basis of the anticancer efficacy of gemcitabine, α-MT and their combination.